Sistem Informasi Kearsipan Dokumen Kepegawaian Pada Universitas Maritim AMNI Semarang - Muhammad Hanif; Felix Andreas Sutanto (Pixel :Jurnal Ilmiah Komputer Grafis, 2021)
There are many archives owned by AMNI Maritime University in Semarang. The archiving system carried out at the AMNI Maritime University Semarang is still not well organized and neat because it is only based on archive classification, so if you have to look for archives such as archive numbers or archive dates, you will experience problems because you have to find the files needed one by one in the filing cabinet. The sequential search algorithm can be applied to the search for employee document numbers at the Maritime University AMNI Semarang and works well as planned. The employee document archive information system at the Maritime University AMNI Semarang can be used to manage the employee document archive more optimally, controlled, well organized and maintained so that the archive is not easily damaged Keywords: Archives, AMNI Maritime University Semarang, Sequential Search Algorithm